(untitled) (Global Journal of Management and Business Research, 2012)
The experience of developed countries tells us that investment in human capital plays an important part in national and regional economic growth.With the advent of knowledge-based economy, there is a growing recognition of the importance of human capital in economic growth. In this paper, starting with the investment of higher education, the relevant Xinjiang#x2019;s data from 1990 to 2009 was used to establish the econometric model, which is used to analyze the importance of human capital investment to the economic growth in Xinjiang. We also indicate that the government should increase the investment in education, so as to fully develop the significant potential of human capital stock.